Does inflammation mediate behavioural alterations in anaesthesia-induced developmental neurotoxicity?. (April 2022) - Neudecker, Viola; Perez-Zoghbi, Jose F.; Brambrink, Ansgar M.
Summary: Anaesthesia exposure early in life potentially impairs neurobehavioural development. A recent study in the Journal investigated the possibility that progesterone mitigates anaesthesia-induced developmental neurotoxicity in neonatal rats exposed to sevoflurane. The novel findings show that the steroid hormone progesterone protects against development of behavioural alterations caused by sevoflurane. The protective mechanism is proposed to relate to anti-inflammatory properties of progesterone, which brings up important questions regarding the role of inflammation in mediating the neurobehavioural alterations in anaesthesia-induced developmental neurotoxicity. We discuss this mechanism and encourage new research that may clarify the underlying mechanisms of progesterone-induced protection and extend these findings into a translational model.